Transcription through the yeast origin of replication ARS1 ends at the ABFI binding site and affects extrachromosomal maintenance of minichromosomes. - Tanaka, S (1994)
When the function of origins of replication in yeast was compromised by placing ARS sequences downstream of strong promoters, ARS activity might have been affected either by transcription or by an altered chromatin configuration induced by the construct. To distinguish between these possibilities, derivatives of the yeast TRP1ARS1 minichromosome were constructed that contained either the DED1 or the PET56 promoter firing against ARS1 (DEDARS and PETARS constructs). PETARS constructs transformed yeast at high frequencies and were maintained as minichromosomes consistent with efficient ARS1 function, but DEDARS constructs transformed at low frequencies and had to be rescued as minichromosomes by insertion of a second ARS (H4-ARS). Chromatin analysis revealed that the ARS1 regions in PETARS and H4-DEDARS constructs were indistinguishable from the ARS1 region of the host TRP1ARS1 circle showing a nuclease sensitive region flanked by a nucleosome. However, RNA-analysis in the ARS region showed high and low levels of transcripts in H4-DEDARS and PETARS, respectively. Transcription elongated through the A, B1, and B2 elements and ended in B3, the binding site for ABFI. We conclude that transcription through ARS1 and not an altered chromatin structure affected ARS activity in these constructs.